Antimicrobial resistance pattern due to oxygen gap at high altitudes - Yang, Zong Chao; Han, Zhang Rui; Li, Xiang Yang; Duan, Ya Bin (Frontiers in Cellular and Infection Microbiology, 2025)
Over the past 10 years, microbial resistance has seriously threatened human life and health, and the treatment of multidrug-resistant bacteria remains a challenge for clinicians, pharmacists, and infectious disease physicians. Bacterial resistance is affected by a variety of factors, such as the environment, economy, and drug abuse. This review compared the differences in bacterial resistance rates between high- and low-altitude areas and explored the relevant mechanisms of bacterial resistance in the low-oxygen environment of plateaus, providing new clinical research ideas for curbing the occurrence of bacterial resistance.